2021
DOI: 10.1093/gbe/evab064
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GC-Biased Gene Conversion on Patterns of Genetic Diversity among and across Butterfly Genomes

Abstract: Recombination reshuffles the alleles of a population through crossover and gene conversion. These mechanisms have considerable consequences on the evolution and maintenance of genetic diversity. Crossover, for example, can increase genetic diversity by breaking the linkage between selected and nearby neutral variants. Bias in favor of G or C alleles during gene conversion may instead promote the fixation of one allele over the other, thus decreasing diversity. Mutation bias from G or C to A and T opposes GC-bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 98 publications
4
21
2
Order By: Relevance
“…We also found that recombination hot-spots had marginally lower GC-content (the opposite is usually observed when biased fixation is a considerable force; Kawakami et al 2013). This is in line with a limited effect of gBGC in Leptidea butterflies (Boman et al 2021) and stays in contrast to findings in several other systems like humans (Fullerton et al 2001, Meunier and Duret 2004), mice (Clément and Arndt 2013), flycatchers (Kawakami et al 2013) and fruit flies (Marais et al 2001), as well as plants (Muyle et al 2011) and yeast (Gerton et al 2000, Kiktev et al 2018). As far as we are aware, there are no other studies that have analyzed the strength of gBGC in butterflies outside the Leptidea genus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also found that recombination hot-spots had marginally lower GC-content (the opposite is usually observed when biased fixation is a considerable force; Kawakami et al 2013). This is in line with a limited effect of gBGC in Leptidea butterflies (Boman et al 2021) and stays in contrast to findings in several other systems like humans (Fullerton et al 2001, Meunier and Duret 2004), mice (Clément and Arndt 2013), flycatchers (Kawakami et al 2013) and fruit flies (Marais et al 2001), as well as plants (Muyle et al 2011) and yeast (Gerton et al 2000, Kiktev et al 2018). As far as we are aware, there are no other studies that have analyzed the strength of gBGC in butterflies outside the Leptidea genus.…”
Section: Discussionsupporting
confidence: 82%
“…Transposable elements characterized as unknown were submitted to CENSOR (Bao et al 2015) for annotation, where any hits with a score < 200 were removed. All predicted sequences were matched against gene annotations using diamond blast 2.0.4 (Buchfink et al 2021), to correct for annotation errors (bitscore > 100). Transposable elements were then annotated in the genome with RepeatMasker 4.1.0, using the predicted library of consensus sequences in wood white and previously characterized TEs in Heliconius melpomene in the RepeatMasker library 4.0.8 (Bao et al 2015).…”
Section: Te Annotationmentioning
confidence: 99%
“…This is likely a consequence of the strong association between recombination rate and chromosome size, since the association with gene density was insignificant when chromosome size was included as an explanatory variable. The observed weak positive association between GC-content and recombination is in agreement with the limited effect of GC-biased gene conversion (gBGC) in butterflies (Boman et al, 2021). We did not find any association between recombination rate and the presence of extended orthogroups, which would be expected if gene duplication is associated with unequal crossing-over.…”
Section: Discussionsupporting
confidence: 80%
“…The observed weak positive association between GCcontent and recombination is in agreement with the limited effect of GC-biased gene conversion (gBGC) in butterflies (Boman et al, 2021). We did not find any association between recombination rate and the presence of extended orthogroups, which would be ex-pected if gene duplication is associated with unequal crossing-over.…”
Section: Patterns Of Recombination Rate Variationsupporting
confidence: 84%
“…More recently, the effect of GC -biased gene conversion (gBGC) has been demonstrated in many taxa (Pessia et al, 2012; Glémin et al, 2014; Galtier, 2021), including Drosophila (Jackson & Charlesworth, 2021). Failing to account for gBGC, when it is present, has been shown to lead to biased inference of selective and demographic forces (Bolívar et al, 2018; Pouyet et al, 2018), or lead to false interpretations about the effect of nonadaptive forces in shaping neutral sequence patterns (Bolívar et al, 2016; Boman et al, 2021). Thus, it is important to incorporate gBGC into the model when inferring adaptive forces and to use GC -conservative mutations for a more accurate representation of the effects of other nonadaptive factors governing neutral genome sequence evolution.…”
Section: Discussionmentioning
confidence: 99%